Communication and Coordination in a Two-Stage Game - Tjaša Bjedov; Thierry Madiès; Marie Claire Villeval (Institute for the Study of Labor (IZA), 2015)
We study the impact of communication on behavior in a two-stage coordination game with asymmetric payoffs. We test experimentally whether individuals can avoid a head-to-head confrontation by means of coordinated strategies. In particular we analyze whether and how quickly a conflict-avoidance take-turn strategy can emerge. First, our results show that players learn to solve the conflict by choosing opposite options at both stages of the game. Second, many adopt a take-turn strategy to sustain coordination over time and alleviate the inequality induced by the asymmetry of payoffs. Third, communication increases the likelihood of conflict resolution even when a single pair member has the right to communicate.
Keywords: C91; D74; L15; H71; 330; coordination; communication; turn taking; conflict; experiment